ANALISIS PENGARUH PEMILIHAN METODE AKUNTANSI TERHADAP PEMASUKAN PENAWARAN PERDANA - Jogiyanto Hartono; Syaiful Ali (Faculty of Economics and Business, Universitas Gadjah Mada, 2002)
IPO (initial public offerings) has been characterized by a lack of publicly available information. In the offerings process, financial statement disclosures are especially critical to the market price-setting process (Neill et al. 1995). In this paper, we examine the accounting methods choices accompanying the initial public offerings of 100 companies that listed at Jakarta Stock Exchange for 1994-1999 periods. Using regression analysis, the methods choice of the sample firms are examined with regard to the company initial offering proceeds.Accounting choice is viewed as a means by which issuers may affect the proceeds of the initial offering. We hypothetized that the issuers with accounting methods result in larger income and asset values (income-increasing methods), has higher initial proceeds than the issuers using income decreasing methods. The accounting methods that we examined are accounting method for inventory valuation and depreciation methods. Other independent variable, which included in the research model are equity book value and ownership signal.Our result indicate no positive association between the initial proceeds from an offering and the selection of accounting methods that result in larger income and asset values. The result is not consistent with the hypotheses of Neill et.al (1995) study, which indicate a marginally positive association.Keywords: IPO, income-increasing methods, income-decreasing methods.